Elongation of achilles tendon represents jump height during hopping - Koyama, K.; Watanabe, K.; Yanagiya, T. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
It is well known that ultrasonography gives directly, but non-invasively, an image of tendon and/or aponeurosis during joint motion (Fukunaga et al.,1996). And the compliant aponeurosis is known to make it possible to jump higher (Kubo et al.,2000). Therefore the purpose of present study is to investigate the relationship between elongation length in the Achilles' tendon during ankle joint motion and jumping height during foot jump.